Desenvolvimento nas regiões do norte da Guiné-Bissau: um olhar sobre o empreendedorismo rural - Siga, Besna (2021)
This research analyzed how rural entrepreneurship can influence development in the regions of Biombo, Cacheu and Oio, located in the northern region of Guinea-Bissau. These regions have socioeconomic potentialities, which need to be used in a rational, equitable way to help leverage the economy and harness the intellectual capital capacities of local actors. The methodology used is qualitative exploratory. The methodological procedure comprises the following phases: the bibliographic survey that allows the construction of the theoretical framework of the study and documentary analysis to identify the views, public policies and actions related to rural development and the promotion of rural entrepreneurship in the study regions; the field research based on the questionnaires previously elaborated and applied to local actors because they are the ones that coexist the daily life of the local reality. The data were treated, grouped and systematized, according to the characteristics of the analyzed organizations, using descriptive statistics in the construction of tables and graphs, assisting in the interpretation. The result shows that the opening of the national market to private initiatives provided by the implementation of the Structural Adjustment Program marks the beginning of entrepreneurship in Guinea-Bissau. Entrepreneurship positively influences the process of socioeconomic development of the regions and the increase in productive activities in these three regions. It is practiced mostly informally and due to the need for survival. Its increase, especially in recent times, is due to the increasing development of lumos practiced in these regions. It is observed that the regions of Biombo, Cacheu and Oio have economic potential to leverage the development process, however, it is necessary to develop broad institutional support to increase family farming and entrepreneurship in rural areas, foster joint actions – government and local actors – focused on entrepreneurial initiatives in rural areas and need to develop through local actors (communities, civil society, political, economic and sociocultural and religious organizations), public policies aimed at improving the quality of life and well-being and, empowering young people and women to go down the path of progress.